HUBUNGAN KOMUNIKASI BELAJAR MENGAJAR TERHADAP HASIL BELAJAR PESERTA DIDIK DI SEKOLAH MENENGAH KEJURUAN NEGERI I KABUPATEN MAJENE - Chuduriah Sahabuddin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2015)
The purpose of this study was to determine the relationship of teaching communication on learning outcomes among students in SMK Negeri 1 Majene district. The method used is the method of correlation, which saw the relations between the variables studied. population in this study were all students in the class of SMK Negeri 1 Majene, the sample in this study amounted to 60 learners. In this study, the instruments used are questionnaires, observations, data were analyzed using descriptive percentages. The results showed that the average score level teacher's communication in learning on the learner in SMK Negeri 1 Majene is high. The results of the students learning outcomes obtained an average value of 70 083. These results illustrate that the average teacher's ability to communicate to students in SMK Negeri 1 Majene district academic year 2015/2016 of the subjects given quite good. Based on the results of correlation r xy value that is equal to 0462 with the alternative hypothesis (Ha) is accepted that there is influence between teachers communication of students learning outcomes.